Fluoride ingestion from toothpaste and diet in 1- to 3-year-old Brazilian children - de Almeida BS, da Silva Cardoso VE, Buzalaf MAR (Blackwell Synergy, 2007)
This study estimated the total daily fluoride intake of 1- to 3-year-old children from diet and dentifrice.